Rediseño de la red de aire comprimido de la empresa gráfica Imprenta Don Bosco C.S.P. - Jacho Loachamin, Edison Mauricio (2016)
This project aims to redesing the compressed air system of Imprenta Don Bosco C.S.P. – Quito´s industrial plant, by means of appropriate choices of the parameters required by the system and proper execution of calculations. In Chapter I, we lay out the scientific and experimental knowledge for the development of the project: the characteristics, the calculation method, and the technical parameters that govern the design – or, in this case, the redesign. Chapter II contains the 3D drawing of the floor plan of the industrial plant, which includes relocation of the machines and space for those which will arrive months later; a total of 25 points of supply: 15 for machines and 10 for maintenance activities. We also acquired and documented information about machines that function using compressed air, with which we determined general working pressure, air quality, and the total volumetric consumption which the system requires for its redesign. Additionally, the selected material for the distribution system is aluminum piping from Legris Transair. For the configuration of the system, workspace divisions are also taken into account. In Chapter III, we detail the necessary equipment and material, with which information we request an estimate, in order to determine the investment required to realize the project.